Enhancing Tourist Visits to Pantai Sembilan Through Effective Instagram Marketing Strategies - Sheren Aurellia Nathania Putri; Zainal Abidin Achmad (Metacommunication: Journal of Communication Studies, 2024)
This study investigates how the Instagram account @pantaisembilan_sumenep uses communication strategies to boost tourist visits to Pantai Sembilan, a well-known beach destination in Sumenep Region. By employing a qualitative descriptive methodology, the research examines the effectiveness of digital marketing through Instagram in promoting tourist attractions. The findings show that the account utilizes various Instagram features to engage potential visitors. These features include posting attractive photos and videos, incorporating relevant hashtags, and using geotags. Additionally, the research highlights the crucial role of strategies such as identifying the target audience, crafting compelling messages, and selecting the right media in attracting both local and international tourists. The study concludes that effective use of social media, particularly Instagram, serves as a vital tool for enhancing Pantai Sembilan's visibility and increasing visitor numbers by providing a platform for interactive and direct marketing.